Management of Information System and Effectiveness of Public Universities in Cross River State, Nigeria - Ojeka, John Ashibene (INTERNATIONAL JOURNAL OF SOCIAL SCIENCES AND MANAGEMENT RESEARCH, 2026)
This study was conducted to investigates the management of information systems and the effectiveness of public universities in Cross River State. Specifically, the study examined the relationship between educational management information system for records management and management of academic planning and Universities effectiveness in Cross River State. A correlational research design was adopted. The study population was 180, comprising all 30 Deans of Faculties and 150 Heads of Departments in the two public universities in Cross River State. Using a census sampling technique, the entire population was involved in the study. The instrument for data collection was an 18-item researcher-developed questionnaire tagged: Management Information System and Effectiveness of Universities’ Questionnaire (MISEUQ), and was validated by three experts from the department(s) of Educational Management, Measurement and Evaluation, University of Calabar. The reliability of the instrument was .85 obtained through Cronbach Alpha reliability method. Descriptive statistics were used to summarize responses, while Pearson Product Moment Correlation tested the hypotheses at a 0.05 significance level. Results revealed a significant relationship between EMIS usage and university effectiveness. The study concluded that proper deployment of EMIS enhances university performance and recommended that institutions equip departments with EMIS tools to facilitate smooth administrative processes.